Newman, Paul: A history of the Hausa language: reconstruction and pathways to the present - (:unkn) unknown (My University, 2023)
Book ReviewWith this remarkable History of the Hausa Language, Paul Newman synthetises his previous publications scattered over 50 years in many articles, and various chapters and footnotes of his reference grammar. Although Paul Newman’s work capitalises on his encyclopaedic knowledge of Hausa and its dialects, Chadic and Afroasiatic languages and their history, his book it is clear, well-written, and easily readable. In conclusion, this History of the Hausa Language is a first, and a must read for specialists in Hausa, Chadic, Afroasiatic and other African languages, as well as for general linguists and typologists.
Keywords: African Research